Elevated Plasminogen Activator Inhibitor (PAI), a Cause of Thrombophilia? – A Study in 203 Patients with Familial or Sporadic Venous Thrombophilia - Engesser, L; Brommer, E J P; Kluft, C; Briët, E (Thrombosis and Haemostasis, 1989)
Two hundred and three patients with venous thrombophilia were investigated in order to find out whether an elevated plasma concentration of plasminogen activator inhibitor (PAI) could be a cause of their tendency to thrombosis. The patients were studied in an asymptomatic period about 3 months after their last thromboembolic episode. PAI activity was found to be elevated in 19 patients (9%), and a corresponding elevation of PAI-1 antigen was observed.In 16 out of the 19 patients with elevated PAI activity, followup could be performed after an additional asymptomatic period of about 1 year: in eight patients the elevation of PAI was transient and in eight it was persistent. Out of the eight patients with a persistent elevation of PAI, seven had a positive family history of thrombosis. Investigation of these families excluded a hereditary elevation of PAI activity in two families. In only two other families was elevated PAI activity also found among family members. The occurrence of elevated PAI activity, however, did not coincide with the occurrence of thrombosis in these individuals: except for the probands, all investigated family members who had a history of thrombosis had a normal PAI activity.We therefore conclude that, at least in our material, familial thrombophilia can not be attributed to an inherited, persistent elevation of the blood level of PAI.
Keywords: Plasminogen activator inhibitor; Venous thrombosis; Thrombophilia